A Study on the Flexural Behaviour of Geopolymer Lightweight Eco-Friendly Concrete Using Coconut Shell as Coarse Aggregate - S. Nithya; K. Gunasekaran; G. Sankar (Advances in Civil Engineering)
This paper presents the flexural behaviour of concrete containing ground granulated blast furnace slag (GGBS) as a binder, manufactured sand (M-sand) as a fine aggregate, and coconut shell (CS) and crushed stone aggregate (CSA) as coarse aggregates. Alkaline activator sodium hydroxide with 10 molarity and sodium silicate were used in a weighing proportion of 1 : 2.5 to produce structural grade concrete. Out of 12 beams cast, 6 were used to study geopolymer coconut shell concrete (GPCSC) beam behaviour and 6 were used to study geopolymer conventional concrete (GPCC) beam behaviour. Data presented include cracking behaviour, ultimate moment capacitates, deflection behaviour, ductility ratio, and end rotation of the beam. Laboratory investigations show encouraging results, and it can be summarized that coconut shell has good potential as a coarse aggregate for the production of structural grade geopolymer lightweight coconut shell concrete.